2019
DOI: 10.3390/nu11081872
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insight into the Interaction between Epigenetics and Leptin in Metabolic Disorders

Abstract: Nowadays, it is well-known that the deregulation of epigenetic machinery is a common biological event leading to the development and progression of metabolic disorders. Moreover, the expression level and actions of leptin, a vast adipocytokine regulating energy metabolism, appear to be strongly associated with epigenetics. Therefore, the aim of this review was to summarize the current knowledge of the epigenetic regulation of leptin as well as the leptin-induced epigenetic modifications in metabolic disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 137 publications
(207 reference statements)
1
23
0
Order By: Relevance
“…Indeed, our in vivo results showed that knockdown of MAT2B attenuated leptin‐induced liver fibrosis in the ob/ob mouse model. Notably, leptin affected epigenetic changes which develop in numerous tissues during metabolic disorders [19] and influenced global DNA methylation in inguinal adipocytes in ob/ob C57BL/6J mice [21]. Our previous results also demonstrated the inductive effect of leptin on Mat2a [33], suggesting that leptin regulated not only Mat2b but also Mat2a in HSCs.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Indeed, our in vivo results showed that knockdown of MAT2B attenuated leptin‐induced liver fibrosis in the ob/ob mouse model. Notably, leptin affected epigenetic changes which develop in numerous tissues during metabolic disorders [19] and influenced global DNA methylation in inguinal adipocytes in ob/ob C57BL/6J mice [21]. Our previous results also demonstrated the inductive effect of leptin on Mat2a [33], suggesting that leptin regulated not only Mat2b but also Mat2a in HSCs.…”
Section: Discussionmentioning
confidence: 72%
“…The progress of HSC activation requires global reprogramming of gene expression, and epigenetic regulation of gene expression is associated with HSC activation [18]. Leptin was revealed to affect epigenetic modifications in metabolic disorders [19]. Our previous results showed that leptin downregulated miR‐122 in HSCs in ob/ob mice [20].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, we examined the miRNA signature in InsR+/− HSCs, which are characterized by an impaired insulin signaling, by analyzing the whole transcriptome, revealing 36 differentially expressed miRNAs compared to wt cells. These deregulated miRNAs were mainly involved in cell proliferation and cancer onset, probably profiling a peculiar pattern of miRNA expression that may orchestrate liver damage progression towards fibrosis and cancer development in IR conditions [4,24,25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…It is perceived as an immunological organ and it releases polypeptides (adipo-/cytokines) as well as metabolites capable of exerting systemic actions, including body weight/energy balance, appetite regulation, glucose homeostasis, insulin signaling, and blood pressure control [65,66]. The first known adipocyte hormone, leptin, whose genetic absence causes massive obesity, suppresses appetite, while other hormones, like adiponectin, have just the opposite effect [67,68]. Adiponectin increases sensitivity of cells to insulin as well as pancreatic β-cells survival and functionality.…”
Section: Hypertrophic Hypoxic and Inflamed White Adipose Tissue-the mentioning
confidence: 99%